Phenotypic and genotypic screening of rice genotypes at reproductive stage for salt tolerance (SAARC Journal of Agriculture, 2018)
Salinity screening of 24 rice genotypes was performed at the reproductive stage for evaluating their salt tolerance level. On the basis of yield and yield components, genotypes were categorized as tolerant, susceptible and moderately tolerant. PBRC-30, Ashfal, Horkuch, STL-20 and Pokkali were found as tolerant while Binadhan-7, S-39 L-11, S-37 L- 27, S-37 L-36 and S-37 L-39 were found as susceptible. Selected three SSR markers viz. RM336, RM21 and RM510 were used to determine salinity tolerance. The genetic diversity was ranges from 0.8194 to 0.8854 with an average of 0.8530. The highest PCI value was 0.8742 and the lowest was 0.8004 from RM510 and RM21, respectively. The UPGMA clustering system generated six genetic clusters. The highest genetically dissimilarity of (Cluster 1) vs (Cluster 2 sub-cluster A) and the crossing would be helpful for salt tolerant rice development. Thus, selected SSR primers and genotypes would be useful in marker assisted breeding, quantitative trait loci (QTL) mapping and gene pyramiding in breeding programmed for improvement of rice for salt tolerance.SAARC J. Agri., 15(2): 69-80 (2017)